6. MENGUNGKAP TINDAK KEKERASAN DI IPDN DAN USAHA PENANGGULANGANNYA - Adhi, Suwanto; Naryoso, Agus (FORUM, 2008)
Violence which took place in IPDN from years to years will never really be revealed something hidden by the IPDN authority home affair department. There are choices to finish the problems on IPDN. First, exchange the rector and lecture, who involved in every incidence in IPDN with the new one. Second, freeze IPDN institution for at least 4 years, so that during that time IPDN won’t be allowed to accept any new students before new curriculum is evaluated by the government.